PEMBUATAN alat penentuan percepatan gravitasi bumi menggunakan metode pendulum berbasis sensor cahaya LDR - Eka Putri Rinanthy (Department of Physics – Universitas Negeri Padang UNP, 2016)
The acceleration of gravity on the second floor at laboratory of electronics and Instrumentation UNP, Padang city by gravity meter is 9.83 m/s2. The acceleration of gravity can be determined through several experiments, including experiments using pendulum method. Parameters of pendulum method still measured manually. The research was designed and created the determination of the earth's gravity acceleration appliance using a pendulum method based on light sensor (LDR). Measurement techniques directly at the output of the sensor LDR as the detector. This research is a laboratory experiment. There are three results of this research. First, performance specifications system consists of a mechanical system that pendulum framework as a holder with two boxes. Box where the circuit box system builder tool and laser as the detector. Second, the Arduino UNO microcontroller is used to process the input data determination earth's gravity acceleration appliance and the results of this research is value the acceleration of gravity on the second floor at laboratory of electronics and Instrumentation UNP, Padang city by determination earth's gravity acceleration appliance is 9,84 m/s2. Third, This instrument have highest precision and accuration, the relative accuracy of the average percentage is 99.77% with an average error of 0.23%, and accuracy average of 0.999 with a standard deviation by an average of 0.017 and a relative error an average of 0.171%.